Osteochondral Fractures After Patellar Dislocation: Current Concepts. (2nd December 2021) - Khan, Shehzaad A.; Baghdadi, Soroush; Carey, James L.; Moores, Thomas S.; Sheth, Neil P.; Ganley, Theodore
Abstract : Osteochondral fractures of the knee occur frequently after acute patellar subluxation or dislocation. They can be challenging to manage because of the difficulty in diagnosing and treating these injuries in a timely fashion, in addition to choosing the optimum fixation method. This review presents the background, considerations for patient evaluation, and the best treatment options available for osteochondral fractures.